The structure of silicon carbide films synthesized by magnetron sputtering - Nussupov, K.Kh.; Beisenkhanov, N.B.; Bakranova, D.I.; Symaiyl, K.; Seitov, B.Zh. (Recent Contributions to Physics, 2018)
This paper is devoted to the synthesis of solid silicon carbide (SiCx) films on the surface of single-crystal silicon (c-Si) with a thin interlayer of amorphous silicon (a-Si) by magnetron sputtering and to establish new regularities in the influence of heat treatment on composition, crystallization processes and structure of layers. A principal difference between this method of synthesis and the traditionally used magnetron sputtering is the 13.56 MHz high-frequency magnetron sputtering of a silicon target and a graphite target. In the deposition mode: rf - 150 W, 13.56 MHz; Ar - 2.4 l/h, 0.4 Pa; 100°C, 10800 s, an amorphous SiСх film with a high density of 3.52 g/cm3 containing nanoclusters with a predominance of shortened SiC bonds absorbing at 860 cm-1, was obtained. Rapid annealing (970°С, 5 min, vacuum) leads to partial disintegration of clusters, an improvement in the structure of the film, the formation of α-SiC, β-SiC and Si nanocrystals and a decrease in the density of the film. Based on the data of X-ray diffraction and density of the film (3,522 and 3,397 g/cm3 before and after annealing, respectively), it was suggested that there are inclusions of diamond and dense clusters.